2017
DOI: 10.1149/2.1431702jes
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Thin Graphitic Carbon Buffer Layers for Electrolytic MnO2for Thin-Film Energy Storage Devices

Abstract: In this study, nanometer thin graphitic carbon coatings were applied as an adhesion layer for the growth of submicron to micron thick electrolytic manganese dioxide (EMD) films for thin-film energy storage devices. The graphitic carbon coating served not only as current collector and adhesion layer between the EMD and the substrate, but also prevented the oxidation of the non-noble TiN substrate during the anodic deposition process. The EMD films consisted of a network of interconnected nanometer-size particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…5 EMD films grown from acidic electrolytes on different substrates were shown to be highly porous (∼50% porosity) consisting of a network of interconnected 5-10 nm nanoparticles. 5,9 However, a very poor adhesion of the EMD films electrodeposited on the noble metal (Pt) coated substrate was observed. The maximum thickness of well-adherent EMD films was limited to 150 nm, with thicker deposits delaminating due to the mechanical film stress.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5 EMD films grown from acidic electrolytes on different substrates were shown to be highly porous (∼50% porosity) consisting of a network of interconnected 5-10 nm nanoparticles. 5,9 However, a very poor adhesion of the EMD films electrodeposited on the noble metal (Pt) coated substrate was observed. The maximum thickness of well-adherent EMD films was limited to 150 nm, with thicker deposits delaminating due to the mechanical film stress.…”
Section: Resultsmentioning
confidence: 99%
“…5 This was shown for example for the 70 nm thick EMD films grown on C/TiN substrate. 9 Unfortunately, only thin (<50 nm) EMD films show good reversible kinetics with sharp Li-ion intercalation and extraction peaks. As opposed to thin films, thicker EMD films display only broad cathodic (at ∼3-3.4 V vs. Li + /Li) and anodic (at ∼2.4-2.6 V vs. Li + /Li) current peaks in their CVs as shown in Figure 11a for EMD films deposited on the different substrates.…”
Section: Porosit Y = 100% · (1 − R B S F Ilm Thickness/s E M F Ilm Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported the deposition of EMD on Si substrates coated with TiN and Pt seed layers as current collectors. It was revealed that TiN gets oxidized during EMD formation and the TiON x passivating layer prevents much more growth of the deposited film [ 10 , 51 , 52 ]. In the case of Pt current collector, EMD films delaminated when reaching a thickness more than 200 nm because of the poor adhesion between Pt and EMD [ 51 ].…”
Section: Introductionmentioning
confidence: 99%